Assessment of Protective Effect of Some Modern Agrochemicals against Ozone-Induced Stress in Sensitive Clover and Tobacco Cultivars - Oleg Blum; Nataliya Didyk; Nataliya Pavluchenko; Barbara Godzik (Journal of Toxicology)
Some modern agrochemicals with antioxidant potential were tested for their protective effect against ozone injury using clover and tobacco ozone-sensitive cultivars as model plants subjected to ambient ozone at two sites (Kyiv city in Ukraine and Szarów village in Poland). All used agrochemicals showed partial protective effects against ozone injury on clover and tobacco. Conducted studies confirmed the effectiveness of modern fungicides belonging to strobilurin group as protectants of sensitive crops against ozone damage. The effectiveness of new growth regulators “Emistym C” and “Agrostymulin” was showed for the first time. Out of the studied agrochemicals, fungicide “Strobi” and natural growth regulator “Emistym C” demonstrated the best protective effects. These agrochemicals present promise for further studies of their possible utilization for enhancement of ozone tolerance of sensitive crops.